2019
DOI: 10.1093/mnras/stz036
|View full text |Cite
|
Sign up to set email alerts
|

Supernovae Kicks in hierarchical triple systems

Abstract: Most massive stars, if not all, are in binary configuration or higher multiples. These massive stars undergo supernova explosions and end their lives as either black holes or neutron stars. Recent observations have suggested that neutron stars and perhaps even black holes receive large velocity kicks at birth. Such natal kicks and the sudden mass loss can significantly alter the orbital configuration of the system. Here we derive general analytical expressions that describe the effects of natal kicks in binari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 118 publications
(188 reference statements)
3
50
0
Order By: Relevance
“…The S-stars, representative of the TE case, display a broader distribution of times compared to the CW disc (which is representative of the GE cases), especially if the L background population induces NRR. The typical inspiral times reported here are compatible to what found by Lu & Naoz (2019), addressing SN kicks in binary stars about a Milky-Way-like SMBH. Lu & Naoz (2019) also suggest GW events can occur over a time-scale as short as a few minutes after the SN, but they do not distinguish between proper EMRIs and direct plunges.…”
Section: Inspiral Time-scalessupporting
confidence: 91%
See 1 more Smart Citation
“…The S-stars, representative of the TE case, display a broader distribution of times compared to the CW disc (which is representative of the GE cases), especially if the L background population induces NRR. The typical inspiral times reported here are compatible to what found by Lu & Naoz (2019), addressing SN kicks in binary stars about a Milky-Way-like SMBH. Lu & Naoz (2019) also suggest GW events can occur over a time-scale as short as a few minutes after the SN, but they do not distinguish between proper EMRIs and direct plunges.…”
Section: Inspiral Time-scalessupporting
confidence: 91%
“…The typical inspiral times reported here are compatible to what found by Lu & Naoz (2019), addressing SN kicks in binary stars about a Milky-Way-like SMBH. Lu & Naoz (2019) also suggest GW events can occur over a time-scale as short as a few minutes after the SN, but they do not distinguish between proper EMRIs and direct plunges. Figure 8 shows the initial versus the final specific binding energy and specific angular momentum magnitude of SN-EMRIs (data points) and of all the COs that remain bound to the SMBH (contours) in two representative cases.…”
Section: Inspiral Time-scalessupporting
confidence: 91%
“…The companion can be a main sequence star, have already transformed into a white dwarf, or become a neutron star or a black hole following a second supernova explosion (Portegies Zwart & Verbunt 1996;Lorimer 2008). However, in most scenarios, the explosion or the kick experienced by the neutron star at birth disrupts the binary system (Hansen & Phinney 1997;Lu & Naoz 2019).…”
Section: Neutron Star Binary System Population Characteristicsmentioning
confidence: 99%
“…Aside from GW captures, GN can be the site of binary mergers induced by interactions with the SMBH (e.g., Antonini & Perets 2012;Naoz 2016;Stephan et al 2016Stephan et al , 2019Hoang et al 2018), via the Eccentric Kozai-Lidov Mechanism (EKL Kozai 1962;Lidov 1962;Naoz 2016). Recently Lu & Naoz (2019) suggested that supernova natal kicks can tend to shrink the post supernova separation. Moreover they showed that these systems are more likely to stay in a triple configuration near an SMBH.…”
Section: Gpc Yrmentioning
confidence: 99%